Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

CosA-SinA+1/CosA+SinA-1=CosecA+CotA

CosA-SinA+1/CosA+SinA-1=CosecA+CotA


 

Grade:11

1 Answers

swapnil sudhir
31 Points
10 years ago

(cosA-sinA)+1/(cosA+sinA)-1

taking conjugate

(cosA-sinA)+1/(cosA+sinA)-1  *  (cosA+sinA)+1/(cosA+sinA)+1

 

multiplying we get

=cos2A-sin2A+2cosA+1/2sinAcosA

=cos2A-sin2A+2cosA+sin2A+cos2A/2sinAcosA                  

on solving we get

 

=2cos2A+2cosA/2sinAcosA

=taking 2 common and divided

 

we get

 

=cosA+cos2A/sinAcosA

 

we can alsom write in the form of

cosA/sinAcosA  +cos2A/sinAcosA

 

on  solving we get

CosecA+cotA =R.H.S

 

 

by swapnil sudhir



Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free